Assessing Accessibility and Transport Infrastructure Inequities in Administrative Units in Serbia’s Danube Corridor Based on Multi-Criteria Analysis and Gis Mapping Tools - Ana VULEVIC; Dragana MACURA; Dragan DJORDJEVIC; Rui Alexandre CASTANHO (Transylvanian Review of Administrative Sciences, 2018)
The Danube Regions, especially the sub-national units of governance, must be ready to play an active role in spatial development policies. A precondition for this is good accessibility and the coordinated development of all transport systems in the Danube corridor. The main contribution of this paper is to provide a multi-criteria model for potential decision making related to the evaluation of transportation accessibility in Serbia’s Danube Corridor. Geographic Information Systems (GIS), based on maps, indicate the existing counties’ transport infrastructures inequities (between well-connected and isolated counties in terms of accessibility to central places). Through the research, relevant indicators have been identifi ed. This provides an outline of transportation perspectives regarding the development achieved and also fosters the increase of transportation accessibility in some peripheral Serbian Danube administrative units – counties (Nomenclature of Territorial Units for Statistics level 3 – NUTS 3).